Genetic and biochemical distinction among Chinese hamster cell emtA, emtB, and emtC mutants. - Chang, S (1983)
Genetic and biochemical experiments have enabled us to more clearly distinguish three genetic loci, emtA, emtB, and emtC, all of which can be altered to give rise to resistance to the protein synthesis inhibitor, emetine, in cultured Chinese hamster cells. Genetic experiments have demonstrated that, unlike the emtB locus, neither the emtA locus nor the emtC locus is linked to chromosome 2 in Chinese hamster cells, clearly distinguishing the latter two genes from emtB. emtA mutants can also be distinguished, biochemically, from emtB and emtC mutants based upon different degrees of cross-resistance to another inhibitor of protein synthesis, cryptopleurine. Two-dimensional gel electrophoretic analysis of ribosomal proteins failed to detect any electrophoretic alterations in ribosomal proteins from emtA or emtC mutants that could be correlated with emetine resistance. However, a distinct electrophoretic alteration in ribosomal protein S14 was observed in an emtB mutant. In addition, the parental Chinese hamster peritoneal cell line of an emtC mutant, and the emtC mutant itself, are apparently heterozygous for an electrophoretic alteration in ribosomal protein L9.